Filling gaps in distribution of Japanese Paraneseuthia Franz: discovery of a new species on Okinawa-jima (Coleoptera, Staphylinidae, cydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2019)
Five currently known Japanese species of the eutheiine genus Paraneseuthia occur on Honshū, Shikoku, Kyūshū, and Ishigaki-jima of the Ryūkyū Archipelago. The southernmost Japanese species was separated from its geographically (and very likely phylogenetically) closest relatives that live on Kyūshū by over a thousand kilometers of the Pacific Ocean. Paraneseuthia zanetae sp. n., found on Okinawa-jima, the largest Ryukyuan island, is described, filling this wide distributional gap. The new species is yet another member of the informal P. paradoxa group, which comprises all Japanese members of this genus that share similar male protibial modifications and a complicated structure of the aedeagus; also two Russian Far Eastern species show close morphological affinities to those inhabiting the Japanese Archipelago.